PROFILE OF CREATIVE THINKING ABILITIES OF CLASS X STUDENTS SURYAMANDALA WAIWERANG PRIVATE VOCATIONAL SCHOOL, SEMESTER II STUDY YEAR 2019/2020 - Familia Novita Mawar; Aloisius Harso; Yasita Embu Ika (ScienceEdu: Jurnal Pendidikan IPA, 2020)
This study aims to determine the profile of student creative thinking ability class X students Suryamandala Waiwerang second semester academic year 2019/2020. This type of research is descriptive research. The population in this study consisted of all students of class X SMAS Suryamandala Waiwerang totaling 62 students and the research sample was 32 students obtained by purposive sampling technique. Furthermore, the data collection technique used non-test techniques, namely questionnaires. Data analysis was carried out with descriptive statistics. The results showed that the students creative thinking skills in class X SMAS Suryamandala Waiwerang had the ability to think very creatively (3,125%) think creatively (9,375%), were quite creative (12,5%), less creative (75%), and not creative (0%). This shows that students creative thinking skills are still very low or less creative.